The development of analytic negatives in Sakhalin Ainu - Elia Dal Corso (CSLI Publications & SLA, 2022)
The aim of this work is to give an overview of negative constructions in Sakhalin Ainu (henceforth SA). By the end of the paper, I will argue that SA negative constructions have developed from a synthetic construction into an analytic one.